Cell therapy in experimental model of inflammatory bowel disease - Mônica Yonashiro Marcelino; Natália Langenfeld Fuoco; Ana Elise Valencise Quaglio; Renata Aparecida de Camargo Bittencourt; Bruna Cambraia Garms; Thaís Helena da Motta Conceição; Luiz Claudio Di Stasi; João Tadeu Ribeiro-Paes (Journal of Coloproctology, 2015)
Inflammatory bowel disease, which mainly involves Crohn's disease and ulcerative rectocolitis, is an inflammatory condition of the mucosa that can afflict any segment of the gastrointestinal tract. Despite the fact that the existing therapies result in improvement in patient's symptomatology and quality of life, there is no curative treatment. Surgical treatment involves complex procedures associated with high morbidity and mortality rates. In this context, cell therapy with stem cells has emerged as a treatment with broad potential applicability. In this study, we intended to verify the efficacy of transplantation of adipose tissue-derived stem cells in rats with intestinal inflammation induced by trinitrobenzenesulfonic acid. The cell population was isolated from the adipose tissue of inguinal region of rats and processed for culture by mechanical dissociation. The animals were evaluated with respect to clinical and biochemical aspects, as well as by macroscopic, microscopic and histological analyses. In the experimental model of bowel inflammation by 2,4,6-trinitrobenzenesulfonic acid, the infusion of adipose tissue significantly reduced the presence of adhesions in the colon and adjacent organs and decreased the activity of myeloperoxidase, a marker of neutrophil infiltration in the injured mucosa. The results suggest that cell therapy with adipose tissue can promote and/or accelerate the regeneration of damaged intestinal mucosa. It is concluded that the presence of adhesions and the determination of myeloperoxidase activity provide indications that adipose tissue can promote and/or accelerate the regeneration of inflammatory bowel mucosa. Resumo: A Doença Inflamatória Intestinal (DII), consistindo principalmente da doença de Crohn e retocolite ulcerativa, é uma condição inflamatória da mucosa que pode acometer qualquer segmento do trato gastrointestinal. Apesar das terapias existentes resultarem na melhora dos sintomas e da qualidade de vida dos pacientes, não há nenhum tratamento curativo. O tratamento cirúrgico envolve procedimentos complexos associados a altas taxas de morbimortalidade. Neste contexto, a terapia celular com células-tronco desponta como opção de tratamento potencialmente promissora. Em função destes aspectos, pretendeu-se, no presente estudo, verificar a eficácia do transplante de células-tronco derivadas do tecido adiposo (ASC) em ratos com inflamação intestinal induzida por ácido trinitrobenzenosulfonico (TNBS). As ASCs foram obtidas por dissociação mecânica do tecido adiposo da região inguinal de ratos e processadas para cultivo. Os animais foram avaliados, considerando-se os aspectos clínicos e bioquímicos, além de análises macroscópica, microscópica e histológica. No modelo de inflamação intestinal induzida por TNBS, a infusão de ASCs reduziu significativamente a presença de aderências entre o cólon e órgãos adjacentes, bem como diminuiu a atividade da mieloperoxidase (MPO), um marcador da infiltração de neutrófilos na mucosa lesada. Os resultados obtidos permitem concluir que a terapia celular com ASCs pode promover e/ou acelerar o processo de regeneração da mucosa intestinal inflamada. Keywords: Inflammatory bowel disease, Stem cells, Adipose tissue, Cell therapy, Palavras-chave: Doença Inflamatória Intestinal, Células-tronco, Tecido Adiposo, Terapia Celular